Infant feeding, HIV transmission and mortality at 18 months: the need for appropriate choices by mothers and prioritization within programmes. - (:unkn) unknown (My University, 2008)
OBJECTIVES: To determine the late HIV transmission and survival risks associated with early infant feeding practices. DESIGN: A nonrandomized intervention cohort. METHODS: HIV-infected pregnant women were supported in their infant feeding choices. Infant feeding data were obtained weekly; blood samples from infants were taken monthly to diagnose HIV infection. Eighteen-month mortality and HIV transmission risk were assessed according to infant feeding practices at 6 months. RESULTS: One thousand one hundred and ninety-three live-born infants were included. Overall 18-month probabilities of death (95% confidence interval) were 0.04 (0.03-0.06) and 0.53 (0.46-0.60) for HIV-uninfected and HIV-infected children, respectively. The eighteen-month probability of survival was not statistically significantly different for HIV-uninfected infants breastfed or replacement fed from birth. In univariate analysis of infant feeding practices, the probability of HIV-free survival beyond the first 6 months of life in children alive at 6 months was 0.98 (0.89-1.00) amongst infants replacement fed from birth, 0.96 (0.90-0.98; P = 0.25) and 0.91 (0.87-0.94; P = 0.03) in those breastfed for less or more than 6 months, respectively. In multivariable analyses, maternal unemployment and low antenatal CD4 cell count were independently associated with more than three-fold increased risk of infant HIV infection or death. CONCLUSION: Breastfeeding and replacement feeding of HIV-uninfected infants were associated with similar mortality rates at 18 months. However, these findings were amongst mothers and infants who received excellent support to first make, and then practice, appropriate infant feeding choices. For programmes to achieve similar results, the quality of counselling and identification of mothers with low CD4 cell count need to be the targets of improvement strategies.
Keywords: African Research